(untitled) (Bangladesh Journal of Botany, 2025)
To investigate the effect of adding microbial agents in the fermentation stage on the quality of tobacco leaves prepared by imitating black tea method. Using Yunyan 87 middle leaves as materials, two microbial agents of Schwanniomyces occidentalis and Bacillus subtilis were sprayed onto the leaves before fermentation, and the effects of different microbial treatments on the main chemical composition, sensory quality, microbial diversity of tobacco leaves were analyzed. The starch content in tobacco leaves treated with S. occidentalis and B. subtilis decreased by 25.00 and 47.64%, and the total pigment content decreased by 46.15 and 30.77%, respectively. Tobacco leaves treated with two microbial agents can increase the characteristic aroma of burnt sweet and sour sweet respectively. The treatment of the two agents can improve the community richness and species diversity of tobacco leaves, and effectively improve the abundance of dominant bacteria such as Firmicutes and Candida. Both exogenous microorganisms can effectively reduce the starch and pigment contents in tobacco leaves, improve the sensory quality of tobacco leaves, improve the diversity of microbial community, and then improve the quality of tobacco leaves prepared by imitating black tea method. Bangladesh J. Bot. 54(3): 783-790, 2025 (September) Special